FEATURES OF INVESTMENT EVALUATION IN CROWDFUNDING- FUNDED PROJECTS - Kholmirzayeva Gulruh Akbarovna; Sarvar Rustamov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This paper examines the specific features of investment evaluation in projects financed through crowdfunding. Unlike traditional investment mechanisms, crowdfunding involves a large number of small investors, which significantly changes the evaluation process and decision-making criteria. The study highlights key factors such as project transparency, reputation of project initiators, information availability, and the role of collective intelligence (crowd wisdom) in assessing investment opportunities. In addition, the research explores the importance of combining financial indicators with social, behavioral, and technological factors when evaluating crowdfunding projects. The findings demonstrate that effective investment evaluation in crowdfunding requires a multidimensional approach that integrates both quantitative and qualitative criteria.